STEMI patients receiving percutaneous coronary intervention for a culprit lesion with coronary artery bifurcation—efficacy and safety of the jailed semi-inflated balloon - Lin, Tzu-Hsiang; Chen, Kuan-Ju; Hu, Yu-Cheng; Chang, Keng-Hao; Lai, Chih-Hung; Liu, Tsun-Jui; Lee, Wen-Lieng; Su, Chieh-Shou (Frontiers in Cardiovascular Medicine, 2023)
Background We aimed to evaluate the efficacy and safety of the ‘jailed semi-inflated balloon technique’ (JSIBT) for side branch (SB) protection in STEMI patients with a culprit lesion involving a coronary artery bifurcation while undergoing emergent percutaneous coronary intervention (PCI). Methods We treated between Jan, 2011 and Jun, 2020, a total of 264 STEMI patients with a culprit lesion that involved a coronary artery bifurcation using primary PCI. In 30 patients, SB was protected by JSIBT (the JSIBT group). In 234 patients, SB was either protected or not protected by a placed wire (the non-JSIBT group). Results In both groups, after PCI procedure, TIMI flows of main vessel (MV) and SB were increased significantly compared with their measurements before the procedure. TIMI flows of post-procedural MV were similar between the two groups. In the JSIBT group, TIMI flows of SB both peri-procedure and post-procedure measurements were significantly greater than the non-JSIBT group. Despite a higher incidence of SB dissection in the JSIBT group, no inter-group difference was found in their total SB complications (like SB dissection, SB occlusion, wire entrapment or balloon rupture/entrapment). While JSIBT was an independent predictor for the SB TIMI 3 flow measured at the end of primary PCI, it was not an independent predictor for SB complications. Conclusion The use of JSIBT as a method of SB protection during primary PCI not only provided better SB protection, but it also had a similar rate of SB complications compared with those with or without prior application of SB wire. This technique may be an effective method of protecting SB for STEMI patients involving coronary artery bifurcation and underwent emergent PCI.